2020
DOI: 10.1103/physrevlett.124.024501
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Electro-osmotic Flow Drives Fluid-Structure Instability

Abstract: We demonstrate the existence of a fluid-structure instability arising from the interaction of electroosmotic flow with an elastic substrate. Considering the case of flow within a soft fluidic chamber, we show that above a certain electric field threshold, negative gauge pressure induced by electroosmotic flow causes the collapse of its elastic walls. We combine experiments and theoretical analysis to elucidate the underlying mechanism for instability and identify several distinct dynamic regimes. The understan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…As a validation of the dynamic numerical solver, we compared the solution of the dynamic numerical simulation (13) (black dots) with the solution of the state-state boundary value problem (23) (gray dots), showing very good agreement. Importantly, the qualitative behavior for the maximum deformation is similar to the one predicted using a plate−spring model [28]. However, the present model allows for the first time to observe the spatial behavior of the elastic sheet as it approaches, and finally contacts the bottom surface.…”
Section: A Deformations Due To Constant Current and Constant Voltage Actuation Modessupporting
confidence: 72%
See 1 more Smart Citation
“…As a validation of the dynamic numerical solver, we compared the solution of the dynamic numerical simulation (13) (black dots) with the solution of the state-state boundary value problem (23) (gray dots), showing very good agreement. Importantly, the qualitative behavior for the maximum deformation is similar to the one predicted using a plate−spring model [28]. However, the present model allows for the first time to observe the spatial behavior of the elastic sheet as it approaches, and finally contacts the bottom surface.…”
Section: A Deformations Due To Constant Current and Constant Voltage Actuation Modessupporting
confidence: 72%
“…trigger instability of the liquid−elastic interface, which acts to diminish the thickness of the film. We have recently demonstrated this concept for the simplified case of a plate−spring model, accounting only for temporal dynamics between two rigid plates [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a computational study by de Rutte et al [221] on electroosmotic flow in a compliant microchannel concluded that a narrow and wide flow conduit can collapse over a range of imposed electric field strengths, and the effect is "exacerbated for soft materials such as PDMS." Boyko et al [222,223] expounded on this idea, showing that "above a certain electric field threshold, negative gauge pressure induced by electro-osmotic flow causes the collapse of its elastic wall." They experimentally demonstrated this novel type of fluid-structure instability and showed that an electroosmotic fluid-structure interaction parameter β ∝ B/(k w Lh 3 0 /η 0 ) (recall section 3.6) controls the (in)stability in a 2D Cartesian configuration as in figure 7(a).…”
Section: Electrohydrodynamicsmentioning
confidence: 99%
“…Innovations in surface probing technologies have enabled the monitoring of several activated biological and engineering surface processes in situ and in real time, such as the conformational change of lysozyme during hydrolysis (Radmacher et al 1994), adaptive alterations related to the functionality of membrane proteins (Müller et al 1999), softness characterization of bubbles, cells and other materials (Steinberger et al 2008;Leroy et al 2012;Guan et al 2017) and more. These problems are hallmarked by exclusive fluid-structure interactions under the broad ambit of elastohydrodynamics (Cawthorn & Balmforth 2010;Mukherjee, Chakraborty & Chakraborty 2013;Pandey et al 2016;Temizer & Stupkiewicz 2016;Naik, Chakraborty & Chakraborty 2017;Rubin et al 2017;Christov et al 2018;Karan, Chakraborty & Chakraborty 2018b;Anand, David & Christov 2019;Wang & Christov 2019;Boyko et al 2020;Karan et al 2020b,c;Sunil et al 2020). Inevitably, the action of a dynamically actuated surface probe apparatus over a deformable surface mediated by a thin viscous fluid layer, typical to a frequently encountered class of applications under the broad ambit of scanning probe microscopy (SPM) (Steinberger et al 2008;Leroy et al 2012;Guan et al 2017), plays a critical role in deciphering the underlying physics in a wide variety of problems of these kinds.…”
Section: Introductionmentioning
confidence: 99%